Polycyclic aromatic hydrocarbon adsorption using β-cyclodextrin functionalized rice husk biochar: Fixed-bed column studies - Rajandran, Prabu; Nasratun, Masngut; Nor Hasmaliana, Abdul Manas; Nur Izyan, Wan Azelee; Siti Fatimah Zaharah, Mohamad Fuzi; Mohamad Abd Hadi, Bunyamin (AIP Publishing, 2023)
Recently, numerous adsorption systems have been examined comprehensively on a laboratory scale to explore the practical feasibility of a particular adsorbent-adsorbate system. However, β-cyclodextrin functionalized rice husk biochar (CD-RHB) as an adsorbent for carbazole removal under fixed-bed adsorption is unreported. This study aimed to characterize the CD-RHB concerning β-cyclodextrin grafting and examine the best-operating conditions for carbazole adsorption onto CD-RHB in a fixed-bed column. Hence, two distinct components participated in producing CD-RHB, β-cyclodextrin and rice husk biochar (RHB). The designed adsorbent (CD-RHB) is systemically analyzed using scanning electron microscopy (SEM) and Fourier-transform infrared (FTIR) spectroscopy. Then, the CD-RHB was utilized in the fixed-bed column studies to identify the best operating conditions for carbazole adsorption capacity. The column parameters such as influent flow rate (14, 15 and 16 mL/min), influent carbazole concentration (1, 2 and 3 mg/L) and CD-RHB dosage (1.0, 1.5 and 2.0 g) have participated in the fixed-bed column studies. Based on the characterization of the designed adsorbent, β-cyclodextrin was successfully decorated and grafted on CD-RHB. Besides, the interpretation of the fixed-bed column studies indicated that the carbazole adsorption capacity was maximum at 14 mL/min influent flow rate, 3 mg/L influent carbazole concentration and 1.5 g CD-RHB dosage. Operating column as stated condition, 9.52 mg/g carbazole adsorption capacity attained from carbazole-contaminated wastewater within 637 min of the adsorption process. In conclusion, CD-RHB packed column shows a remarkable capability of treating carbazole in an aqueous solution.